VISUALISASI DALAM PERANCANGAN DAN PELAKSANAAN PRAKTIKUM BIOLOGI SEKOLAH - Oktavia Safitri; Evi Suryawati; Darmadi Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Knowledge about the development of learning with the practicummethod is one of the initial assets of Biology Education students to becomeprofessional biology teachers. But in reality, there are still students who have notmastered the competencies related to practicum activities. Based on these problems,this study aims to produce an independent learning resource in the form ofvisualization in the design and implementation of school biology practicum in the formof a video equipped with a guidebook. This research was conducted at the PMIPALaboratory FKIP Riau University, SMAN 8 Pekanbaru and SMAN 15 Pekanbaru inApril-December 2020. The type of research used is Research and Development (R&D)which refers to the ADDIE model. The instruments used in this study were validationsheets and response questionnaires. The results of the visualization product validationobtained an average score of 3.57 (video) and 3.39 (guidebook) with very validcategories. The results of the limited trial phase I obtained an average value of 3.64(video) and 3.72 (guidebook) with very good categories. Meanwhile, the results of thesecond phase of the trial obtained an average value of 3.43 (video) and 3.47(guidebook) with very good categories. Based on the results of the validation andtesting, it shows that the visualization products in the design and implementation ofthe developed school biology practicum can be used as a source of independentlearning for prospective biology teachers.Key Words: Implementation, Design, Practicum, Visualization